Orthonychiurus azoricus - Nunes, Rui (2021)
JUSTIFICATION: Orthonychiurus azoricus is an Azorean-endemic species described from S. Miguel island (Azores, Portugal) (Jacquemart, 1974), at an unknown location. Possibly it has a very small Extent of Occurrence (EOO = 4 km²) and Area of Occupancy (AOO = 4 km²); but the present situation of this species needs to be further assessed, and further research is needed into its population, distribution, threats, ecology and life history. Conservation of native habitats and streams could potentially aid this species' conservation. Based upon the lack of data regarding this species population, distribution, threats and ecology, this species is assessed as Data Deficient (DD).